The impact of STEM on the growth of wealth at varying scales, ranging from individuals to firms and countries: The performance of STEM firms during the pandemic across different markets. (February 2023) - Podobnik, Boris; Dabić, Marina; Wild, Dorian; Di Matteo, Tiziana
Abstract: Researchers have not yet reached consensus on whether there is a difference in performance between STEM and non-STEM firms across different financial markets during economic expansion and through economic downturns, such as pandemics and recessions. It is unclear as to whether STEM or non-STEM firms, but also graduates with STEM or non-STEM education contribute more, less, or equally to economic inequality. By analysing total wealth at varying scales, ranging from individuals, to firms, to entire countries, we demonstrate that the Zipf exponent, serving as a proxy for wealth inequality, persistently ramps up as the scale of a system increases. At an individual level, analysing the Zipf plots separately for the world's richest individuals with STEM and non-STEM graduation degree, we begin by demonstrating that STEM education contributes more to inequality than non-STEM. At a firm level, in contrast to the DAX and CAC40 indexes, for firms comprising the S&P 500 index, the average growth rate of STEM constituents has been significantly higher than those calculated for non-STEM constituents during the most recent economic expansion and the coronavirus pandemic. This insight is particularly useful for the financial sector. Secondly, we demonstrate a functional dependence between a country's number of patents and its STEM graduates. Finally, motivated by the fact that the U.S. heavily surpasses the E.U. in terms of Venture Capital, we model wealth inequality at different scales of the economy. Highlights: By examining the Forbes lists of richest individuals at the world level over the last two decades, we find that the Zipf plot ) of the world's STEM billionaires significantly increases in wealth inequality. We demonstrate a functional dependence between a country's number of patents and STEM graduates. The model combines Simon's traditional rich-gets-richer model with the rich-gets-richer competition mechanism. In the model, we empirically establish that the U.S. STEM-orientated companies demonstrate better performance than non-STEM.